Dryland Social-Ecological Systems in Changing Environments - Fu, Bojie; Stafford-Smith, Mark (Springer Nature Singapore : Imprint: Springer, 2024)
This open access book prepared by a joint working group committed to critical research on dryland social-ecological systems (SESs) presents a timely synthesis of up-to-date knowledge in various thematic fields relevant to dryland SESs. It aims to organize key salient concepts and establish a conceptual framework relevant to the interdisciplinary and cross-cultural understanding of dryland SESs, which have specific contexts and a geographically representative structure. Through synthesizing research across the world and analyzing scientific evidence for good practices, it has the potential to promote collaboration among global researchers as well as communication with policy makers, managers, and practitioners for dryland ecosystem management to promote sustainability. It calls for synergies between different sectors and countries to achieve Sustainable Development Goals in drylands. .